Performance evaluation of plant-produced warm mix asphalts containing RAP and RAS. (24th November 2017) - Arshadi, Amir; Steger, Richard; Ghabchi, Rouzbeh; Zaman, Musharraf; Hobson, Kenneth; Commuri, Sesh
Abstract : In the present study, rutting performance, cracking resistance, and durability of five plant-produced asphalt mixes containing 12% reclaimed asphalt pavement (RAP) and 3% recycled asphalt shingles (RAS) and produced with different warm mix asphalt (WMA) technologies were evaluated through characterisation of extracted asphalt binder and performance tests conducted on asphalt mix specimens. For all of the extracted and recovered asphalt binders, continuous grades and difference between critical low temperatures, Δ T cr parameter, were determined from performance grading and a Glover–Rowe (G–R) damage zone was evaluated at 45°C and 10 rad/s. It was revealed that the application of a rejuvenating agent (RA) significantly reduced high PG grade of the overall asphalt binder. The binder test results also indicated that the chemical-additive-based WMA technology had an advantage over the foaming-based technology in terms of asphalt binder durability. Furthermore, the application of RA improved the asphalt binder durability. Comparison of G–R parameters of the recovered asphalt binders showed that using RA and lowering virgin binder high PG true grade improve the overall binder ductility and damage resistance. Asphalt mix performance tests included dynamic modulus (DM), flow number, and semi-circular bend. The DM test data indicated that the application of RA and lowering the virgin binder high PG grade lowered the mix stiffness at low frequencies. Comparison of the methods to compensate the effect of highly aged RAP and RAS binders indicated that the mix prepared with RA and one level high PG grade drop performed better than the mix prepared by dropping the PG grade by two levels in terms of cracking resistance and rutting performance. The findings give credence to utilisation of RAs and softer virgin binders in balanced RAP/RAS mix design approaches.